Influence of Chitinous Waste on Soil Bacterial Community: Biofertilizer Effect and Antifungal Activity. (2015) - Aïzi, Djamel Eddine; Cheba, Ben Amar
Abstract: Today, the chitinous wastes are used by several companies to produce chitin and chitosan, which are used in various biotechnological applications, particularly in the agricultural sector which is a key sector for sustainable development. Improving the quality of the plant production requires an improvement in its rhizospheric microbial composition, which called Plant Growth Promoting Rhizobacteria (PGPR), the role of these microorganisms not only the improving the quality of nutrients present in the rhizosphere, but also assure the plant protection against phytopathogenic agents. The objective of this work is to study the effect of chitinous waste on Triticum durum (wheat) rhizospheric microflora, by mixing (W/W) the wheat soil with chitinous waste at different concentration. Twentieth days of Monitoring, showed a significant effects on the soil microflora and pH. The results of the first ten days of treatment revealed in elevation in bacterial number with Bacillus genus dominance and absolute absence of fungi even saprophytic or phytopathogenic, whereas the results of the last ten days were characterized by the diversity of wheat rhizospheric microflora with appearance of Plant Growth Promoting Rhizobacteria such as N2 fixing bacteria and those involved in plant protection.